2022
DOI: 10.3758/s13423-022-02117-w
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral vision in real-world tasks: A systematic review

Abstract: Peripheral vision is fundamental for many real-world tasks, including walking, driving, and aviation. Nonetheless, there has been no effort to connect these applied literatures to research in peripheral vision in basic vision science or sports science. To close this gap, we analyzed 60 relevant papers, chosen according to objective criteria. Applied research, with its real-world time constraints, complex stimuli, and performance measures, reveals new functions of peripheral vision. Peripheral vision is used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(21 citation statements)
references
References 188 publications
1
19
0
1
Order By: Relevance
“…Building on the experimental work by Minamoto et al ( 2015 ) and Sorqvist et al ( 2016 ) wherein the distraction potential of task-irrelevant visual stimuli was powered under lower load, it is then plausible that the decline in workload experienced during partially-automated driving may have increased the distraction potential of roadside billboards. This intepretation would also be consistent with the literature on cognitive tunnelling whereby a reduction in the drivers’ useful field of view is observed under greater cognitive load (Strayer et al, 2011 ; Vater et al, 2022 ). For example, Reimer ( 2009 ) had participants complete a driving task alongside a secondary cognitive task.…”
Section: Discussionsupporting
confidence: 89%
“…Building on the experimental work by Minamoto et al ( 2015 ) and Sorqvist et al ( 2016 ) wherein the distraction potential of task-irrelevant visual stimuli was powered under lower load, it is then plausible that the decline in workload experienced during partially-automated driving may have increased the distraction potential of roadside billboards. This intepretation would also be consistent with the literature on cognitive tunnelling whereby a reduction in the drivers’ useful field of view is observed under greater cognitive load (Strayer et al, 2011 ; Vater et al, 2022 ). For example, Reimer ( 2009 ) had participants complete a driving task alongside a secondary cognitive task.…”
Section: Discussionsupporting
confidence: 89%
“…‘Looked but did not see errors’ are among the most frequent causes of accidents (Brown, 2002). Vater et al (2022) also reported, distraction inherently reduces a driver’s awareness of the driving environment, as it puts driving-relevant information outside the visual field. Other researchers also reported that, while distracted drivers rely more on peripheral vision for lane-keeping, they are less able to process and react to the information that peripheral vision provides them (Gaspar et al, 2016; Lin & Hsu, 2010).…”
Section: Discussionmentioning
confidence: 96%
“…'Looked but did not see errors' are among the most frequent causes of accidents (Brown, 2002). Vater et al (2022) also reported, distraction inherently reduces a driver's awareness of the driving environment, as it puts driving-relevant information outside the visual field.…”
Section: In-vehicle Task Performancementioning
confidence: 96%
“…The longer RT with high sensory interference may indicate that the participants were switching attention between the obstacle in the walkway and the light cue when it was away from the obstacle. Alternatively, increased RT may indicate that participants adopted a gaze strategy observed in sports, called gaze anchor : foveating on one area of interest (e.g., obstacle) and relying on peripheral vision to monitor another area (e.g., light cue location in upper visual field) [ 47 ]. Since RT is longer when the stimulus is in the peripheral versus central visual field [ 48 , 49 ], increased RT may have resulted from monitoring the light cue location with peripheral vision.…”
Section: Discussionmentioning
confidence: 99%